Ultrasonographic evaluation of oral submucous fibrosis patients: A noninvasive diagnostic approach - Aditya Dupare; Apeksha Dhole; Mukta Motwani (Wolters Kluwer Medknow Publications, 2018)
Background: Oral submucous fibrosis (OSMF) is one of the most common premalignant conditions seen in the Indian population. It affects all parts of oral cavity including buccal and labial mucosa, tongue, and soft and hard palate. Ultrasonography is a noninvasive, nonionizing technique, readily available, cost effective, and better accepted by patients. In USG, OSMF shows alteration in submucosal thickness and vascularity overlying the bands leading to reduced peak systolic velocity (PSV). These changes cannot be assessed during clinical and histological examination. In advanced cases, OSMF can be diagnosed based on the typical clinical picture but to assess prognosis and to monitor the response to treatment; USG can be a better diagnostic tool of choice. Aim: To evaluate the submucosal thickness and PSV using USG in OSMF patients. Materials and Methods: In total, 40 OSMF patients were selected from departmental OPD divided into four groups (OSMF stages I, II, III, and IVA) equally. They were subjected to ultrasonographic evaluation for submucosal thickness and PSV of buccal and labial mucosa bilaterally. Results: On statistical analysis, the results were found highly significant (P-value < 0.05). There is significantly increase in the submucosal thickness and decrease in PSV among the OSMF stages I, II, III, and IVA, respectively. Conclusion: USG is found to be very effective tool for the diagnosis of OSMF as it is noninvasive modality which does not cause any discomfort to the patient and provides qualitative and quantitative information of the condition.